Warehouse Performance Improvement at Linfox Logistics Indonesia - Pratama, Riyan Galuh; Simatupang, Togar M (The Indonesian Journal of Business Administration, 2013)
The objective of this research is to provide alternative solutions for Linfox Logistics Indonesia (LLI) in facing warehouse performance issues. The main warehouse performance indicators called Customer Case Filling on Time (CCFOT) and Case Picking Productivity failed to achieve the target. Several analyses were carried out regarding current dispatch process, value stream mapping, and root causes identification. The results find that much waste occurred in dispatch process. Proposed improvements include reengineering business process and implementing ABC cycle counting. Using Monte Carlo simulation, each solution is examined to find expected lead time and customer case filling on time. Expected cases picking productivity is estimated by eliminating the waste. It is shown that reengineering dispatch process and implementing ABC cycle counting could eliminate all wastes, shorten delivery lead time, and make both KPIs surpass the target.Ã‚Â Keywords: warehouse, dispatch process, Monte Carlo simulation, ABC cycle counting, Linfox Logistics IndonesiaÃ‚Â